Exploring shared leadership in public organizations: evidence from the educational arena - Juliana Carvalho; Filipe Sobral; Juliana Mansur (Revista de Administração Pública, 2020)
Abstract Collective leadership, reflecting the representative and participatory character of bureaucracies, is known to have a good fit for public organizations. Despite the importance of the topic, very few studies have examined what triggers the emergence of shared or participative leadership in public organizations and how these plural forms of leadership translate into team outcomes. To fill this gap, this study explores whether the existence of an organizational climate characterized by participative safety (a climate characterized by shared purpose, social support, and voice) can facilitate the emergence of collective forms of leadership, such as shared leadership. Further, we investigate if shared leadership ultimately influences an important organizational outcome: voluntary turnover. To test our model, we conducted a field study with 96 public schools and more than 1,000 teachers of the public educational system of the city of Rio de Janeiro. Our results highlight the importance of the existence of a favorable organizational climate for the emergence of shared leadership and provide evidence of the positive effects of this type of leadership on reducing turnover ratings among public teachers.